Gowri Ganesha Festival in Karnataka - (:unkn) unknown (My University, 2023)
Festivals bring happiness, joy and satisfaction to people's lives. During festival times, the temples, cultures and religious centres perform various pujas according to traditions followed over the year, creating a lot of positive energy. Each festival is unique and special in its way, and Gowri and Ganesha festival, popularly called Gowri Ganesh Habba, is a significant festival in Karnataka. In Kruthayuga, Parvati and Parameshwara were said to be in a serious discussion one day. Gradually the debate took a sensual tone. At the same time, many deities and angels visit them in Kailasa, their abode. As a result, Parvati shies away from Parmeshwara, and due to his heightened sense of love, he lets go of essence, and it falls on the earth. Goddess earth retains some of it and leaves the rest in the river Ganga. After nine months, Earth gives birth to a girl child and names her Gauri. She brings gold from the land of Varuna(Water God) and covers the child Gowri with gold ornaments. This is how Gowri was called Swarna Gowri. As a symbol of health, happiness, and wealth, sixteen different items such as turmeric, vermillion, bangles, fruits, betel leaf, jaggery, grains and lentils etc. are placed inside the container in the bamboo soups and distributed among themselves. They seek blessings from each other as every other married woman is considered part of the divine gowdi. As the festivals come closer, Artists paint the idol with attractive colours and keep them ready for sale. According to our Indian calendar, Ganesha Chaturthi falls on the day of Suddha Chaturthi of Bhadra Padamasha. In other words, it arrives in either September or October every year. The Ganesha idol is installed in most houses and public places during the festival. Devotees decorate both sides of the road and illuminate them with colourful lights. On the day of the festival, people buy the Ganesha idols from the market and bring them home with all delight and emotion. The children enjoy the most on this occasion. The family's elders wear fresh clothes while installing the idol of Ganesha on decorated varieties of colourful flowers. The family members then light up the lamps and chant the mantra. At home, women sing devotional songs and perform aarti before their favourite deity. In North Karnataka, the Ganesha festival is celebrated differently. At festival time, Ganesh mandap is decorated with lanes. During pre-independence days, The Ganesha festival was marked as a family festival, but over the period, this festival has become a state festival. On the day of Visarjana, The Ganapati Bappa is offered back to water and soil.
Keywords: Gowri Ganesh Festival in Karnataka; Swarna Gowri; Ganapathi; Shudda chaturthi Bhadrapada masa; Ganesh mantap; Immersion of Idols of Ganesha and Gowri; Kannada